Transient and d.c. analysis of the operation mechanism of light-emitting electrochemical cells - Gozzi, Giovani; Santos, Lucas F. [UNESP]; Faria, Roberto M. (Epl Association, European Physical Society, 2012)
Light-emitting electrochemical cells (LECs) made of electroluminescent polymers were studied by d.c. and transient current-voltage and luminance-voltage measurements to elucidate the operation mechanisms of this kind of device. The time and external voltage necessary to form electrical double layers (EDLs) at the electrode interfaces could be determined from the results. In the low-and intermediate-voltage ranges (below 1.1 V), the ionic transport and the electronic diffusion dominate the current, being the device operation better described by an electrodynamic model. For higher voltages, electrochemical doping occurs, giving rise to the formation of a p-i-n junction, according to an electrochemical doping model. Copyright (C) EPLA, 2012